2019
DOI: 10.1155/2019/4606219
|View full text |Cite
|
Sign up to set email alerts
|

A Bioinformatic Approach for the Identification of Molecular Determinants of Resistance/Sensitivity to Cancer Thermotherapy

Abstract: Application of heat above 43°C and up to 47°C, the so-called “thermal ablation” range, leads to tumor cell destruction either by apoptosis or by necrosis. However, tumor cells have developed mechanisms of defense that render them thermoresistant. Of importance, the in situ application of heat for the treatment of localized solid tumors can also prime specific antitumor immunity. Herein, a bioinformatic approach was employed for the identification of molecular determinants implicated in thermoresistance and imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 81 publications
(72 reference statements)
0
7
0
Order By: Relevance
“…Whereas, through bioinformatic approach, Duzgun et al identified a series of molecules that determine the thermoresistance and immunogenic cell death in thermotherapy through estimating the percentage of the two kinds of denatured proteins. They found that thermoresistance along with ICD both existed in a broad temperature windows, and that average T m (50% of the protein is unfolded) of DAMPs (63.42°C) is remarkably higher compared to the thermal ablation temperature due to the function to interact with their pattern recognition receptors (PRRs) even under thermal stress (49). Although the suitable temperature for maximized immunity remains unclear, these models offer ways to rationally explore suitable conditions to exploit hyperthermia.…”
Section: Hsps Are Among the Most Important Damps Induced By Hyperthermiamentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas, through bioinformatic approach, Duzgun et al identified a series of molecules that determine the thermoresistance and immunogenic cell death in thermotherapy through estimating the percentage of the two kinds of denatured proteins. They found that thermoresistance along with ICD both existed in a broad temperature windows, and that average T m (50% of the protein is unfolded) of DAMPs (63.42°C) is remarkably higher compared to the thermal ablation temperature due to the function to interact with their pattern recognition receptors (PRRs) even under thermal stress (49). Although the suitable temperature for maximized immunity remains unclear, these models offer ways to rationally explore suitable conditions to exploit hyperthermia.…”
Section: Hsps Are Among the Most Important Damps Induced By Hyperthermiamentioning
confidence: 99%
“…Studies have found that certain gene mutations, such as KRAS, are more sensitive to hyperthermia as they exhibit sustained ERK signaling hyperactivation and increased Wingless/Integrated (WNT)/beta-catenin signalling (132). Moreover, using a bioinformatic approach, a series of molecules have been identified as determinants of resistance/sensitivity to thermotherapy (49). The results of the two studies offer ways for accurate selection when treated with hyperthermia.…”
Section: Conclusion and Future Challengesmentioning
confidence: 99%
“…The expression of BCL2 may reflect the enhancement of cell death and immunogenicity risk signals in transplantation and constitute a risk factor for poor transplantation results ( 31 ). Further, HSPA4 is expressed in heat resistance, damage signaling molecules (DAMPs), and ICD ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results of KEGG analysis suggest that ATO treatment mainly mobilizes the immune system in AML xenograft mice, and the MAPK signaling pathway and NOD-like receptor signaling pathway was signi cantly activated. Previous studies have found that these two signaling pathways were crucial to the initiation of pyroptosis and induction of cancer cell death [26,42,43] . The DEPs in the two signaling pathways included p38, p53, cathepsin B (CTSB), and NLRP3.…”
Section: Discussionmentioning
confidence: 99%
“…and the activation of p53 can in turn promote GSDME transcription [26,42,43] , which may convert apoptosis into pyroptosis when it is highly expressed in cancer cells [22] . Our data have shown that ATO could stimulate the release of HMGB1 and up-regulate the expression levels of p38 and p53, indicating that the upregulation of p53 by ATO treatment is probably a consequence of the promotion of p38 and HMGB1, thus promoting GSDME transcription to induce pyroptosis.…”
Section: Discussionmentioning
confidence: 99%